2020
DOI: 10.1038/s41598-020-59249-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) on N-turnover, the N2O reductase-gene nosZ and N2O:N2 partitioning from agricultural soils

Abstract: Nitrification inhibitors (NIs) have been shown to reduce emissions of the greenhouse gas nitrous oxide (n 2 O) from agricultural soils. However, their N 2 O reduction efficacy varies widely across different agroecosystems, and underlying mechanisms remain poorly understood. To investigate effects of the NI 3,4-dimethylpyrazole-phosphate (DMPP) on N-turnover from a pasture and a horticultural soil, we combined the quantification of N 2 and N 2 O emissions with 15 N tracing analysis and the quantification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…However, their mode of action is not known at the molecular level, and they are thought to act as chelators of the essential copper atom present in the active site of AMO, an unproven hypothesis, while other more potent inhibitors are known but not marketed for field applications [ 5 ]. Moreover, their efficacy to reduce nitrogen losses has been shown to be highly variable and depending on many environmental conditions [ 29 , 30 ]. In any case, it is important to consider the environmental toxicity, the solubility as well as the concentrations required to modulate nitrification [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their mode of action is not known at the molecular level, and they are thought to act as chelators of the essential copper atom present in the active site of AMO, an unproven hypothesis, while other more potent inhibitors are known but not marketed for field applications [ 5 ]. Moreover, their efficacy to reduce nitrogen losses has been shown to be highly variable and depending on many environmental conditions [ 29 , 30 ]. In any case, it is important to consider the environmental toxicity, the solubility as well as the concentrations required to modulate nitrification [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same fertilization rate was also used in previous field experiments of the ZeoLIFE project [28] and in laboratory studies involving the same soil and zeolites [22]. As an additional factor, in a separate batch, each treatment received 2.916 µ g −1 of the nitrification inhibitor DMPP in liquid form, corresponding to 0.6% of the fertilizer added, according to [35,38]. This dosage also reflects the amount of DMPP that is commonly contained in granulated formulations [51,54].The tested treatments thus resulted in the following six combinations in four replicates:…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the environmental conditions, substantial amounts of the potent greenhouse gas N 2 O are emitted from soil, unless the whole N 2 O is converted to N 2 by the enzyme N 2 O reductase encoded by nosZ. The abundance of the functional gene amoA and the genes nirS and nosZ can give indications on the efficiency of the respective processes [38][39][40][41].…”
Section: Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that DMPP has several obvious advantages over other currently used NIs. This compound is highly effective at inhibiting soil nitrification, reducing N2O emissions, increasing N fertilizer efficiency and crop yields [25,26] . Previous studies have shown that the application of DMPP in intensive vegetable fields significantly reduced the cumulative soil N2O emissions by 75% [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%